Transumbilical single-site laparoscopic treatment of small intestinal cavernous hemangioma in child: a case report - Kong, Meng; Liu, Weiqiang; Bai, Yuexia; Jia, Jinhua; Liu, Chuanyang; Zhang, Shisong (Frontiers in Oncology, 2024)
Background: While hemangiomas are the most commonly occurring benign vascular tumors, their occurrence in the gastrointestinal system is rare. This case report presents a unique instance of small intestinal hemangioma in a pediatric patient.Case Description: A 21-month-old girl was admitted to the hospital with a history of "recurrent blood in the stool for one year and anemia for five months." Upon evaluation at our facility, abdominal color ultrasound and enhanced CT scans revealed a protruding mass in the wall of the small intestine, leading to a preliminary diagnosis of small intestinal hemangioma. Subsequent single-site umbilical laparoscopic exploration identified a tumor measuring approximately 6cm × 2.5cm×1.2cm on the jejunum wall. Consequently, segmental resection of the intestine was performed, and the postoperative pathological diagnosis confirmed cavernous hemangioma.Conclusions: Small intestinal hemangiomas, particularly in pediatric patients, are exceptionally rare and challenging to diagnose as the cause of gastrointestinal bleeding prior to surgery. Hence, small intestinal hemangiomas should be considered in such cases. Laparoscopic surgical resection emerges as the optimal approach for addressing small intestinal hemangiomas.